Indonesia : Detailed Assessment of Observance of IMF Code of Good Practices on Transparency in Monetary and Financial Policies. (IMF Staff Country Reports; Country Report ;, 2012)
This paper discusses key findings of the Financial Sector Assessment Program (FSAP) covering the transparency of monetary policy in the Republic of Indonesia. There is a reasonably high degree of transparency in Indonesia's monetary policy, with much progress having been made over the last decade. The paper highlights that the adoption of an inflation targeting (IT) framework in 2005 significantly enhanced the effectiveness of Bank Indonesia in conveying its objective to the wider public.